Human apolipoprotein A-I gene expression increases high density lipoprotein and suppresses atherosclerosis in the apolipoprotein E-deficient mouse. - Plump, A S (1994)
Atherosclerosis is a complex disease with both genetic and environmental determinants. Apolipoprotein (Apo) E-deficient mice have been created that are highly susceptible to atherosclerosis. In order to assess the role of human apolipoprotein (hApo) A-I and high density lipoprotein (HDL) in atherosclerosis susceptibility, transgenic mice overexpressing the hApo A-I gene were crossed with Apo E-deficient mice. Apo E-/-, hApo A-I mice with two-fold elevation in HDL cholesterol have markedly diminished atherosclerosis with less fibroproliferative lesions by 8 months of age. A strong reciprocal relationship between HDL cholesterol levels and atherosclerosis was found with HDL levels accounting for 78% of the observed variance in mean lesion area. The effect of HDL on atherosclerosis resistance was independent of non-HDL cholesterol.